Dekonstruksi Pola Penelitian Skripsi Mahasiswa S1 Akuntansi Fakultas Ekonomi dan Bisnis Unissula Periode 2020 - 2024 Melalui Pendekatan Bibliometrik - Nunky Figo Setyawan; Chrisna Suhendi (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— This study deconstructs undergraduate thesis research patterns at the Faculty of Economics and Business, Sultan Agung Islamic University (2020-2024) using bibliometric analysis. It aims to identify topic trends, analyze thematic clusters, and evaluate research gaps in accounting student theses. Using a descriptive-quantitative approach, the research analyzed 1,405 theses through purposive sampling. Secondary data (titles, keywords, authors, publication years) were processed using Publish or Perish and VOSviewer for conceptual network visualization. Analysis focused on keyword co-occurrence frequency, topic clustering, and identifying trends and research gaps. Results revealed 12 thematic clusters from 164 keywords (minimum 5 occurrences). Findings show saturation in conventional topics (profitability, company size, corporate governance) while contemporary topics (Special Allocation Funds, Islamic contracts, accountability, audit tenure, religiosity, audit quality) remain under-explored. Overlay visualization demonstrates topic development stagnation with publication concentration in 2022, though sustainability reporting and financial literacy increased in 2023. This research provides a comprehensive map of accounting thesis research trends for curriculum development, improved academic guidance, and alignment with industry needs. The study highlights the need to diversify research topics beyond traditional areas and encourage exploration of emerging themes relevant to current business and accounting practices